On the Theory of Order Statistics of the Flexible Lomax Distribution - Farrukh Jamal; Muhammad Ijaz; Ghulam Mustafa; Sadaf Khan; Shakaiba Shafiq (Operations Research and Decisions, 2024)
This paper studies the flexible Lomax distribution's order statistics with graphical and numerical findings. Along with the quantitative measurements, some plots are furnished, including those for the skewness and kurtosis measures. We will dwell on the numerous results that relate to statistics of moments of order. We consider the single and product moment of order statistics from the new distribution. Further, we establish some recurrence relation for single moments of order statistics. We have sought to apply the derived relations to empirically evaluate the moments of smallest (largest) order statistics to establish well-known moments and related measures. For order statistics of a flexible Lomax distribution, exact analytical expressions of entropy, residual entropy, and past latent entropy are determined. (original abstract)